Nanodevices Versus Bacteria in a Box: The Correspondence between Classical Electrodynamics and the Quantum Mechanics Path Integral - Nieto-Chaupis, Huber (2020)
We use the Quantum Mechanics path integral to describe bacteria spatial dynamics inside a box that that is limited by constant electric potentials. While this potential can be materialized to some extent of being a physical representation of macro-phage cell the bacteria behavior is also driven by the Jackson's electric potential. In this manner, the resultant repulsive or attractive electric force might drive the spatial displacement of bacteria to accomplish the task of motility and chemotaxis. The path-integral language seen a stochastic tool appears as an interesting option to model bacteria and Antimicrobial peptides agents when both of them are in a random struggle in space-time. In addition its complementary to Electrodynamics support tits usage inside of the Microbiological territory. Our hybrid approach turns out to be precise with an error of order of 3%.